1977
DOI: 10.1136/bmj.1.6058.422
|View full text |Cite
|
Sign up to set email alerts
|

Why hypertensive patients vary in their response to oral debrisoquine.

Abstract: weeks (P< 0-01) in those who responded well and by six weeks (P<005) in those who showed no remission. Among patients with normal prolactin values the release of prolactin after thyrotrophin-releasing hormone was significantly greater in those with no remission than in those who responded to tamoxifen. Responses in those with hyperprolactinaemia were reduced to about half the control values, and again this change occurred faster in those who were successfully treated. Patients therefore seem to have a better c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…The clinical features of thirteen of these have been reported (Silas et al, 1977); those of the two remaining subjects were similar. Tablet counts confirmed that each subject took more than 95%o of the tablets prescribed.…”
Section: Subjectsmentioning
confidence: 83%
See 1 more Smart Citation
“…The clinical features of thirteen of these have been reported (Silas et al, 1977); those of the two remaining subjects were similar. Tablet counts confirmed that each subject took more than 95%o of the tablets prescribed.…”
Section: Subjectsmentioning
confidence: 83%
“…Almost 70% of the variance in response to debrisoquine may be related to differences in its urinary recovery and plasma concentration and there is a significant inverse correlation between the urinary recovery of its 4-hydroxy metabolite (HD) and the fall in blood pressure. Thus a poor response can be overcome by increasing the dose (Silas, Lennard, Tucker, Smith, Malcolm & Marten, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Its prescription has however been complicated by a large interpatient variation (40-fold) in optimal dose requirement. \, 12 We have shown that variation in response to debrisoquin is largely due to genetically determined variations in metabolism. 4 Debrisoquin is metabolized and inactivated in man mainly by alicyclic 4-hydroxylation, with a small proportion oxidized in the aromatic ring to yield 4 phenolic metabolites, namely, 5-, 6-, 7-, and 8-hydroxydebrisoquin.3 The extent to which the drug is hydroxylated in the 4-position in Caucasian subjects is controlled by a single autosomal gene locus and demonstrates polymorphism,8 There are 2 apparent phenotypes within the popUlation: The first small recessive phenotype (8% of Caucasians) is characterized by an almost total inability to 4-hydroxylate the drug and is designated the poor metabolizer (PM) phenotype.…”
mentioning
confidence: 99%
“…Debrisoquine is an antihypertensive agent whose widely variable plasma concentrations and blood pressure-lowering effect over a narrow dose range are largely determined by its polymorphic oxidation (Silas et al 1977). This is now more of academic than of clinical significance, since debrisoquine and other adrenergic neurone blocking agents are now rarely used in the treatment of hypertension because of the risk of orthostatic hypotension and other adverse effects.…”
Section: Cardiovascular Drugsmentioning
confidence: 98%